A study on the factors that influence the effectiveness in training and development program at Office of State Secretary Kedah (PSUK Kedah) / Siti Salbiah Shahril Anuar - Shahril Anuar, Siti Salbiah (2013)
Training and development refer to programs designed to help new employees adjust to the workplace successfully. In addition, they include the formal ongoing efforts of corporations and other organizations to improve the performance and self-fulfillment of their employees through a variety of methods and programs. This paper attempts to identify the significant determinants of training effectiveness. By constructing a hypothetical research model to investigate the effect of the instructor competence, trainee’s traits and method of training (independent variable) towards training effectiveness (dependent variable), a survey questionnaire were distributed to employees in Office of State Secretary (PSUK Kedah) who have attended training programs. A Likert-type scale has been developed and tested in this study. The results of the research were obtained by using four methods of analysis which was reliability test, frequency distribution, Pearson correlation and backward regression. The process of analyzing and interpreting of the data was presented through tables. The results of this study show that instructor competence is strongly affects on the effectiveness in training and development program. Therefore this research could help the organizations especially PSUK Kedah in correctly identifying the training requirements and suitability of training method or program, for new and existing employees.